Analisis Kemampuan Motorik Halus Siswa Kelas II SDN 50 Pekanbaru - Angraini, Sofia; Antosa, Zariul; Munjiatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of fine motor skills in supporting various learning activities of elementary school students. Fine motor skills play an important role in activities involving the use of small muscles, such as coloring, cutting, and pasting. This study aimed to describe the fine motor skills of second-grade students at SDN 50 Pekanbaru. This research employed a descriptive qualitative approach involving 11 second-grade students as the research subjects. Data were collected through interviews with students and the classroom teacher, as well as documentation of students’ work. The findings revealed that the fine motor skills of second-grade students at SDN 50 Pekanbaru had developed fairly well. The students demonstrated good eye-hand coordination; however, activities requiring higher levels of precision, such as accuracy, neatness, and finger dexterity, still required further stimulation. These findings indicate that the fine motor skills of the second-grade students at SDN 50 Pekanbaru have developed, but have not yet reached an optimal level across all indicators. Therefore, continuous stimulation and practice through various activities involving coordination, accuracy, and finger dexterity are needed to further enhance students’ fine motor skill development.